2012
DOI: 10.1038/leu.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of graft-versus-host disease after reduced-intensity conditioning allogeneic stem cell transplantation for acute myeloid leukemia: a report from the Acute Leukemia Working Party of the European group for blood and marrow transplantation

Abstract: This report investigated the impact of graft-versus-host disease (GVHD) on transplantation outcomes in 1859 acute myeloid leukemia patients given allogeneic peripheral blood stem cells after reduced-intensity conditioning (RIC allo-SCT). Grade I acute GVHD was associated with a lower risk of relapse (hazards ratio (HR) ¼ 0.7, P ¼ 0.02) translating into a trend for better overall survival (OS; HR ¼ 1.3; P ¼ 0.07). Grade II acute GVHD had no net impact on OS, while grade III-IV acute GVHD was associated with a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
133
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 36 publications
11
133
3
2
Order By: Relevance
“…reported that among patients with pretransplantation minimal residual disease, OS after CBT was as favorable as HCT with HLA‐matched unrelated donor and much higher than HCT with HLA‐mismatched unrelated donor, and the probability of relapse was lower in the cord‐blood group than in either of the other groups, which indicated that cord blood may have a stronger GVL effect than other graft sources. In this study, we found that both relapse rate and cGVHD rate were lower in the MMAC group, which seemed to be inconsistent with the previous reports as some authors believed that GVL effect was closely related to cGVHD 38, 39, 40. Nevertheless, most of these studies were designed for HCT with matched sibling donors, haploidentical‐related donors and unrelated donors, the GVL effects of CBT may work in a different way.…”
Section: Discussioncontrasting
confidence: 83%
“…reported that among patients with pretransplantation minimal residual disease, OS after CBT was as favorable as HCT with HLA‐matched unrelated donor and much higher than HCT with HLA‐mismatched unrelated donor, and the probability of relapse was lower in the cord‐blood group than in either of the other groups, which indicated that cord blood may have a stronger GVL effect than other graft sources. In this study, we found that both relapse rate and cGVHD rate were lower in the MMAC group, which seemed to be inconsistent with the previous reports as some authors believed that GVL effect was closely related to cGVHD 38, 39, 40. Nevertheless, most of these studies were designed for HCT with matched sibling donors, haploidentical‐related donors and unrelated donors, the GVL effects of CBT may work in a different way.…”
Section: Discussioncontrasting
confidence: 83%
“…It highlights the role of ATG, which protects against acute and chronic GVHD [30]. Unfortunately, this positive effect is counterbalanced by an increased incidence of relapse, as observed in previous reports [31,32], eventually resulting in similar survival rates. In this report, high-risk patients according to the last CIBMTR disease risk classification were found to harbor higher aGVHD, higher relapse, and impaired survival rates compared with other groups.…”
Section: Discussionmentioning
confidence: 52%
“…25 However, this seems to be counterbalanced to some extent by more standard myeloablative conditioning and a less frequent use of in vivo T-cell depletion in this very group, both being assumed to be associated with a higher antileukemic activity. 26,27 In conclusion, this study demonstrates that adjuvant, unmanipulated DLT from related and unrelated donors are safe and highly effective in preventing post-transplantation relapse in highrisk AML. Eligible patients treated with aDLT have an excellent chance for long-term survival in spite of high-risk disease.…”
Section: Discussionmentioning
confidence: 99%